Análisis comparativo de planes de estudio de ingeniería biomédica: el caso de la Universidad Autónoma Metropolitana - Urbina Medal, Edmundo G; Azpiroz Leehan, Joaquín (Revista Mexicana de Ingenieria Biomedica, 2007)
A comparative analysis among different curricula in Biomedical Engineering schools is carried out in order to evaluate probable changes in the Biomedical Engineering curriculum at Universidad Autónoma Metropolitana. The distribution of the types of courses, the number of hours required and the requirements to obtain a BME degree are studied. The conclusions show that the BME curriculum up to 2006 is extremely rigid and excessive. Different modifications are suggested, such as flexibilization, offering a larger series of electives that are up to date and in accordance with the lines of research that are being followed at the University